Effects of different doses of methylprednisolone therapy on acute respiratory distress syndrome: results from animal and clinical studies - Shukun Hong; Chao Jian; Hongye Wang; Xincheng Wang; Luchuan Xing; Lujun Qiao (BMC Pulmonary Medicine, 2022)
Abstract Background The optimal dose of glucocorticoids for acute respiratory distress syndrome (ARDS) is uncertain. This study aimed to evaluate the effects of different doses of methylprednisolone on sepsis-induced acute lung injury (ALI) rats and a cohort of moderate and severe ARDS patients. Methods ALI rats, challenged with lipopolysaccharide, were randomly received intraperitoneal injection of normal saline (model group) and different doses of methylprednisolone (0.5, 2, 8 mg/kg, named as low-, moderate- and high-dose group, respectively) for 5 days. The body weight changes of rats, inflammatory factors in bronchoalveolar lavage fluid (BALF), lung wet/dry ratio, histopathological score, and the mRNA expressions of glucocorticoid receptor α (GRα), GRβ and nuclear factor-κB (NF-κB) were measured. Forty moderate and severe ARDS patients were treated with standard of care or plus different doses of methylprednisolone (40, 80, 120 mg/day, named as low-, moderate- and high-dose group, respectively) for 5 days. Clinical outcomes were PaO2/FiO2 ratio and C-reactive protein (CRP) level at day 5, intubation rate, hospital stay, 28-day mortality, and adverse events rate. Results In animal experiment, different doses of methylprednisolone could increase the body weight of rats, and reduce inflammatory factors in BALF and the degree of lung injury compared with model group. The efficacy of methylprednisolone at moderate-dose was better than that at low-dose, but was equivalent to that at high-dose, which was consistent with the differential changes in the mRNA expression of GRα, GRβ and NF-κB. In clinical study, the moderate-dose group was associated with higher PaO2/FiO2 ratio and lower CRP level. No significant difference in other clinical outcomes among groups was detected. Conclusions This study showed that the efficacy of methylprednisolone in ARDS treatment was not always dose-dependent due to the differential regulation of related receptors. The moderate-dose of methylprednisolone may be the potential optimal dose for ARDS treatment, which needs to be further verified by larger clinical trials.